(untitled) (Research, Society and Development, 2023)
Botulinum toxin has a wide range of applications in both the medical and aesthetic fields. However, it is important that individuals wishing to undergo such procedures understand the possible associated risks and choose qualified professionals to carry them out safely and effectively. The aim of this study is to analyze the complications caused by Botulinum Toxin A, describe its mechanism of action and recommendations for aesthetic application. Methodology: This is an integrative literature review aimed at understanding the complications linked to its use in facial aesthetics. Results and Discussion: The complications reported, such as double vision, sixth nerve palsy, respiratory tract infections, granulomas and eyelid ptosis, are rare events and highlight the importance of continuing training for qualified professionals, the use of safe guides and the administration of safe facial doses to minimize complications. The need for personalized treatment is also evident, taking into account the patient’s physiology and ethnicity. Precautions such as maintaining a sterile environment and informing patients about possible adverse effects are also discussed. Final considerations. Although botulinum toxin is an effective tool for cosmetology, its application requires in-depth knowledge and technical skills, professionals need to keep up to date with best practices and the latest guidelines to ensure patient safety and treatment quality.